A New Topological Perspective on Quantization in Physics - Rahimizadeh, Hooman; Sholar, Stan; Berg, Michael (Communications in Mathematics and Applications, 2012)
We propose a new characterization of classical quantization in physics in terms of sheaf cohomology on the site of spacetime as a smooth 4-manifold. The perspective of sheaf cohomology is motivated by a presentation of the Aharonov-Bohm effect in terms of the integration of differential forms.